2011
DOI: 10.1055/s-0039-1698900
|View full text |Cite
|
Sign up to set email alerts
|

Use of an Implant O-Ring Attachment for the Tooth Supported Mandibular Overdenture: A Clinical Report

Abstract: Retention of a mandibular denture can be achieved by an implant-retained or natural tooth-retained bar and stud attachment in the anterior segment of the mandible. The same design principles holds true for both implant-retained and tooth-retained methods of anchoring the bar and stud attachment. A simple and cost effective treatment for more complex implant overdenture is the concept of conventional tooth-retained overdentures. When few firm teeth still remain in a compromised dentition, preservation of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…2,3,[5][6][7][8][9][10] The keystone of success for an overdenture treatment is the selection of strategic abutments with endodontic and periodontal therapy to receive the attachment. 4 The use of ball attachment provides a superior retention as well as it acts as a shock absorber and stress redirector. It is effortless to insert and remove and it is convenient for most of the patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3,[5][6][7][8][9][10] The keystone of success for an overdenture treatment is the selection of strategic abutments with endodontic and periodontal therapy to receive the attachment. 4 The use of ball attachment provides a superior retention as well as it acts as a shock absorber and stress redirector. It is effortless to insert and remove and it is convenient for most of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…There are various attachment systems available for tooth-supported overdenture. 3,4 Their retention tends to remain more or less the same, hence increasing the compliance of the patient. Attachment systems help to connect either individual teeth or splinted teeth to prosthesis.…”
Section: Introductionmentioning
confidence: 99%
“…1 In addition, tooth -supported attachments allow better occlusal distribution and absorption of masticatory forces. 3 A variety of overdenture attachments are available. Based on resiliency, they can be divided into resilient or rigid, with the former being more efficient in protecting abutment teeth from occlusal forces.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of design, overdenture attachments can be classified as studs or bars, depending on whether the denture base is connected to each tooth individually or to splinted abutment teeth, respectively. 3 Ball -type attachments constitute a valuable option to improve the retention and support of overdentures. Some studies document their efficiency, suggesting that this type of attachment is the most appropriate due to the minimal transference of forces to the abutment teeth.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the rehabilitation alternatives of partially or completely edentulous patients such as the use of dental implants, fixed prosthesis, removable partial or complete dentures, the overdenture offers a viable and simple alternative and has been demonstrated to be efficient in these clinical situations (3,4). The literatures reported that the use of selected teeth in strategic positions can greatly improve the final treatment result in terms of overdenture stability and retention (5,6).…”
Section: Introductionmentioning
confidence: 99%